Investigação aplicada à gestão de risco geológico-geotécnico, para fins de planejamento urbano. Caso piloto: "Erosão na cidade de São Carlos" - Acosta, Ileana Carolina Osorio (2020)
The need to deepen the analysis of geological processes, of combined origin (natural-anthropogenic), in urbanized areas requires a constant review of the methodologies to be used. In this sense, the present research had as objective the construction of a methodological proposal of insertion of geotechnical data of subsoil in the elaboration of a map of susceptibilities to linear erosive processes, in a microbasin of the city of São Carlos-SP, like a fundamental tool in risk management in urban areas. Initially, the evolutionary assessment of the susceptibility and risk maps for erosion and landslide already existing in the state of São Paulo was carried out, and three major groups were identified: geotechnical maps, susceptibility maps and risk mapping. Within the cartographic groups of risk and susceptibility, the studies that included erosive features in their results were highlighted, since erosive processes are the central point of our research work. This survey favored the choice of multicriteria analysis in the development of our methodological proposal. Then, the characterization of the physical environment, the watershed of the Mineirinho river, proceeded through the selection of topographic, anthropic variables and soil attributes (subsoil) considered important in the development of erosive processes. Being chosen: the slope, the curvature of the slopes, the coverage and use of the soil, the vertical variation of the textures of the unconsolidated materials, as well as the geotechnical parameters of resistance to penetration, cohesion, friction angle and specific mass for each material, for consider them relevant in the context of this research. For the evaluation of the geotechnical characteristics of the superficial materials occurring in the studied basin, laboratory and in situ tests of resistance to penetration were carried out, using the STOLF impact penetrometer, as well as the collection and use of pre-existing data from drilling and wells carried out in the study region; constituting the first effort to create a geological-geotechnical database in the UFSCar DECiv. Finally, the 1: 15.000 scale erosion susceptibility map was generated in the Mineirinho river watershed in the city of São Carlos-SP, with detail (1: 2.000 scale) in a region that is currently developing erosion; resulting in the predominance of the "high susceptibility" class, correctly delimiting the most degraded areas, which confirms the influence of evaluated conditioning factors (topographic, textural, geotechnical and anthropogenic) in the potentiation of erosive features.